The Influences of Authentic Leadership, Meaningful Work, and Perceived Organizational Support on Psychological Well-Being of Employees in Sport Organizations - Mansouri, Hossein; Pyun, Do Young; Md Husin, Maizaitulaidawati; Gholami Torkesaluye, Sajad; Rouzfarakh, Abdullah (Journal of global sport management (Print), 2024)
This study aimed to examine the effects of organizational experience on psychological capital and psychological well-being in sport organizations. The organizational experience was measured using three variables which are authentic leadership, meaningful work, and perceived organizational support. The role of psychological capital as a mediator towards psychological well-being was also tested. The subjects of this study included employees of sport and youth organizations in the southern Iran. A PLS-SEM analysis was used to test the hypotheses. The results showed that authentic leadership, meaningful work, and perceived organizational support positively affected psychological well-being. Psychological capital served as a mediator between the organizational variables and psychological well-being. This study is the first attempt to assess the role of psychological capital and identify the type of leadership in Iranian sport organizations.